A tér és a látvány lehetőségei a magyar esztétizmusban - Bednanics, Gábor (Studia Litteraria, 2013)
The intersection of culture, mediality and literature is accessible by the discourse of landscape and lyrical landscape descriptions. These Modernist spatial depictions also make us understand that the media of visual arrangements are necessary for literary articulations as well. Picture and language, seeing and speaking are not opposites but they can come forth correlated. From the 19th century, it is also obvious that Romanticism made the landscape a special space for poetry by means of the new visual challenges. In my paper, I point out some Hungarian tendencies of that subject, especially in the poetry of Mihály Babits and Gyula Juhász, regarding to the Impressionist tradition.